WEIRD SPACES, IN BETWEEN: REPRESENTING THE NORMALISATION OF THE CRISIS IN CONTEMPORARY GREEK CINEMA - Poupou, Anna (Design/Arts/Culture, 2024)
Taking as a starting point the idea of capitalist realism, as formulated by Mark Fisher and associated with the power, or the inabilities of contemporary cinema to imagine alternative realities, this paper explores the representations of crisis through the elements of space and class in contemporary Greek films that were produced within the context of the Weird Wave and reveal the process of “normalization” of the crisis.